2021
DOI: 10.1038/s41598-021-02803-0
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Transport Factor 2 (NTF2) suppresses WM983B metastatic melanoma by modifying cell migration, metastasis, and gene expression

Abstract: While changes in nuclear structure and organization are frequently observed in cancer cells, relatively little is known about how nuclear architecture impacts cancer progression and pathology. To begin to address this question, we studied Nuclear Transport Factor 2 (NTF2) because its levels decrease during melanoma progression. We show that increasing NTF2 expression in WM983B metastatic melanoma cells reduces cell proliferation and motility while increasing apoptosis. We also demonstrate that increasing NTF2 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Exogenous NUTF2 suppressed cell proliferation (Figure 5F), as seen in melanoma 40 . The K4Q mutation rescued this phenotype (Figure 5F), suggesting that K4 acetylation blocks the growth-inhibitory activity of NUTF2.…”
Section: Nutf2 Mediates Crosstalk Between the Egfr And Erα Signaling ...mentioning
confidence: 66%
“…Exogenous NUTF2 suppressed cell proliferation (Figure 5F), as seen in melanoma 40 . The K4Q mutation rescued this phenotype (Figure 5F), suggesting that K4 acetylation blocks the growth-inhibitory activity of NUTF2.…”
Section: Nutf2 Mediates Crosstalk Between the Egfr And Erα Signaling ...mentioning
confidence: 66%
“… 58 Additional work in mice has shown that increasing the expression of nuclear transport factor 2 in metastatic melanoma cells reduces cell motility and metastasis. 59 Kratzsch et al demonstrate that targeting tumor growth and tumor cell interactions with vasculature using inhibitors of mammalian target of rapamycin and vascular endothelial growth factor receptors may delay development of symptomatic spinal metastasis, though therapeutic efficacy was only mild. 60 Collectively, these studies suggest that elucidating the molecular underpinnings of the metastatic cascade could reveal novel approaches for prophylactic treatment of metastatic spinal melanoma.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…With respect to disease, nuclear morphometrics and chromatin condensation state are used as cancer biomarkers ( Damodaran et al. , 2019 ; Vukovic et al. , 2021 ).…”
Section: Discussionmentioning
confidence: 99%